Hubungan Antara Harga Diri dengan Pengambilan Keputusan untuk Kawin pada Wanita Bali Usia Dewasa Awal - Wiraswati, Anak Agung Ketut Sri; Supriyadi, Supriyadi (Jurnal Psikologi Udayana, 2015)
Early adulthood have a need to develop an intimate relationship through marriage (Santrock, 2002). Before deciding to hold the marriage, they conducted a series of decision-making process. Self-esteem is one of the variables that involved in individual decision-making. The main purpose of this study is to investigate the direction and strength of relationship between self-esteem and decision-making to get married among early adulthood Balinese women. A total of 196 Balinese women aged between 20 up to 40 years old and married becoming the subject of this quantitative correlational research. The sampling technique was two-stage cluster sampling. Measuring instruments used are the self-esteem scale (27 items; rxx` = 0,883) and decision-making to get married scale (16 items; rxx` = 0,824). Data were processed using Pearson Product Moment analysis, simple linear regression, and one-way ANOVA analysis. Statistical analysis show, there is significant correlation between self-esteem and decision-making to get married among early adulthood Balinese women (r= 0,723; p= 0,000). The coefficient of determination obtained for 0,523 which means that 52,3% of the variance that occurs in the decision-making to get married variable can be explained by the variance in self-esteem variable. F test analysis found that the mean scores for decision-making to get married did not differ significantly when assessed from the level of education (F= 1,169; p= 0,323) and birth order (F= 0,601; p= 0,550).   Keywords: Self-esteem, decision-making to get married, Balinese women, early adulthood